Preconceptional evaluation of women with recurrent pregnancy loss: the additional value of assessing vascular and metabolic status - Denise H. J. Habets; Veronique M. M. M. Schiffer; Lisa P. A. Kraneburg; Femke J. W. de Krom; Irem Gürtekin; Bo E. van Bree; Ron J. T. van Golde; Lotte Wieten; Marc E. A. Spaanderman; Salwan Al-Nasiry (BMC, 2022)
Abstract Background A majority of recurrent pregnancy loss cases (RPL) remains unexplained. We hypothesized that complications in vascular and metabolic status may guide towards underlying problems that also predispose to RPL and that the number of pregnancy losses is related. Methods A retrospective study in 123 women with either a history of low-order RPL (2-3 pregnancy losses) or high-order RPL (≥ 4 pregnancy losses) and 20 women with a history of uncomplicated pregnancy (controls) was performed. Vascular status was assessed by measuring hemodynamic parameters, determining abnormal parameters and analyzing their contribution to the circulatory risk profile (CRP). In a similar way, metabolic status was assessed. Metabolic parameters were measured, used to determine abnormal parameters and analyzed for their contribution to the metabolic syndrome (MetS). Results No major differences were observed in vascular or metabolic parameters between women with RPL and controls. There was no relation with the number of pregnancy losses. However, when analyzing the presence of abnormal constituents, more than 80% of women with RPL had at least one abnormal constituent of the CRP. While only 27% had one or more abnormal constituent of the MetS. Conclusions The presence of abnormal circulatory factors prior to pregnancy, and to lesser extent constituents of the metabolic syndrome, may predispose to RPL and offer new insights to its pathophysiology.